2016
DOI: 10.1182/blood-2016-05-715870
|View full text |Cite
|
Sign up to set email alerts
|

A trial of unrelated donor marrow transplantation for children with severe sickle cell disease

Abstract: • Children with sickle cell disease engrafted unrelated donor marrow after reduced intensity conditioning.• A high incidence of GVHD and associated mortality compromised safety of the trial.Children with sickle cell disease experience organ damage, impaired quality of life, and premature mortality. Allogeneic bone marrow transplant from an HLA-matched sibling can halt disease progression but is limited by donor availability. A Blood and Marrow Transplant Clinical Trials Network (BMT CTN) phase 2 trial conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
158
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 55 publications
1
158
2
2
Order By: Relevance
“…Under the circumstances, when counseling patients for transplantation, it is important to balance the potential benefits of long-term survival as a result of a curative treatment against the risks for mortality from transplant-related complications and the potential risk for severe GVHD, which adds to the burden of morbidity and mortality. 29,30 Standard of care (ie, nontransplant therapies) has very low toxicity, but it offers no cure for the underlying disease, and the risk for death is higher later in life; the expected mortality is 4.4 per person-years. 31,32 As a consequence, the ideal comparison between these 2 very different treatments would be a randomized trial of the treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Under the circumstances, when counseling patients for transplantation, it is important to balance the potential benefits of long-term survival as a result of a curative treatment against the risks for mortality from transplant-related complications and the potential risk for severe GVHD, which adds to the burden of morbidity and mortality. 29,30 Standard of care (ie, nontransplant therapies) has very low toxicity, but it offers no cure for the underlying disease, and the risk for death is higher later in life; the expected mortality is 4.4 per person-years. 31,32 As a consequence, the ideal comparison between these 2 very different treatments would be a randomized trial of the treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Shenoy et al 49 reported 29 patients with SCD who underwent matched unrelated donor HSCT. Patients received alemtuzumab starting 22 days before transplant, fludarabine, and melphalan.…”
Section: Discussionmentioning
confidence: 99%
“…16 Current standards for HLA matching for transplantation of bone marrow and peripheral blood from unrelated adult volunteer donors for non-malignant diseases support matching donors to recipients at HLA-A, -B, -C and –DRB1 at the allele-level. 7 Survival was highest after HLA matched transplants at 65%, and lower after transplants mismatched at one allele (57%; p=0·07) and two alleles (46%; p=0·001).…”
Section: Introductionmentioning
confidence: 99%